GAMBARAN KEMATANGAN KARIR PADA MAHASISWA TINGKAT AKHIR - Devi Jatmika; Linda Linda (Universitas Bunda Mulia, 2015)
Higher education students’ are in the late adolescent period. In this period they must accomplish some developmental tasks specifically regarding education and working issues. As last term students in their career exploration stage, they have to focus on working issues, thus they need career maturity. This research aims to describe career maturity of last term students of “X” University by using quantitative research method. The instrument of this research was Career Maturity Inventory (CMI) Field data was collected from 118 last term students. The result showed that 51% students were in very low career maturity, 10% were in low career maturity, 66.9% were in moderate career maturity, and 17.8% were in high career maturity. Some additional results revealed, there were differences of career maturity between students who have working experiences and do not have working experiences (sig 0.060 > 0.05). There were no differences of career maturity based on gender (0.233> 0.05). From the content analysis of open-ended questionnaire results showed the meaning of career for students were: determine future, occupation, and success symbol. Some students did career planning such as studying, getting working experiences, and finding job information. Problems they feel in career planning like do not have working experiences, feel confused to choose, and financial capital for making business. They also mentioned their own strengths were competency, skills, attitude and working experiences. Some weaknesses they feel such as lack of competency and skills, having lack of working attitude, and lack of self confidence. In sum, last term students’ exhibited moderate to high career maturity. Working experiences and evaluation of strengths may predict students’ career maturity. Keywords: Career maturity, last term students, career exploration, working